Hunting for gravity waves in non-orographic winter storms using 3+ years of regional surface air pressure network and radar observations - L. R. Allen; L. R. Allen; S. E. Yuter; S. E. Yuter; M. A. Miller; L. M. Tomkins; L. M. Tomkins (Atmospheric Chemistry and Physics)
Atmospheric gravity waves (i.e., buoyancy waves) can occur within stable layers when vertical oscillations are triggered by localized heating, flow over terrain, or imbalances in upper-level flow. Case studies of winter storms have associated gravity waves with heavier surface snowfall accumulations, but the representativeness of those findings for settings without orographic precipitation has not been previously addressed.